Microfinancing, governance, and performance: a South Asian perspective - Saeed, Asif; Javed, Attiya Y.; Noreen, Umara (Universidad ESAN. ESAN Ediciones, 2018)
Purpose – This paper aims to investigate the relationship between microfinance institutions (MFIs) governance and performance. Design/methodology/approach – Using a sample of 215 MFIs from six South Asian countries over the period from 2005 to 2009, the authors examine the effect of chief executive officer (CEO) duality, board size, female CEO, urban market coverage, bank regulation and lending type on financial and social performance of MFIs. Findings – The findings provide evidence that, on the one hand, empowered CEO, large board size and individual lending improve the MFI financial performance and, on another hand, bank regulation and serving in the urban market have a significant association with MFIs’social performance. In an additional analysis, the authors also test this relationship before, during and after the financial crisis of 2007. During crisis period, MFIs’ individual lending reduces the operational cost and bank regulation increases the average loan size in South Asian MFIs. Originality/value– Those studies that are presented in the literature review conclude their result on the bases of global, European, East African and specific to some countries sample. There is no study presented in the whole literature on South Asian sample, in which all countries really face the problem of poverty.

Objetivo - Este documento tiene como objetivo investigar la relación entre la gobernanza y el desempeño de las instituciones de microfinanzas (IMF). Diseño / metodología / enfoque - Utilizando una muestra de 215 IMF de seis países del sur de Asia durante el período de 2005 a 2009, los autores examinan el efecto de la dualidad del director ejecutivo (CEO), el tamaño de la junta, la directora ejecutiva femenina, la cobertura del mercado urbano, la regulación bancaria y el tipo de préstamos sobre las finanzas. y desempeño social de las IMF. Recomendaciones - Los hallazgos proporcionan evidencia de que, por un lado, el CEO empoderado, el tamaño grande del directorio y los préstamos individuales mejoran el desempeño financiero de las IMF y, por otro lado, la regulación bancaria y el servicio en el mercado urbano tienen una asociación significativa con el desempeño social de las IMF. En un análisis adicional, los autores también prueban esta relación antes, durante y después de la crisis financiera de 2007. Durante el período de crisis, los préstamos individuales de las IMF reducen el costo operativo y la regulación bancaria aumenta el tamaño promedio de los préstamos en las IMF del sur de Asia. Originalidad / valor - Los estudios que se presentan en la revisión de la literatura concluyen su resultado sobre las bases de muestra global, europea, del este de África y específica de algunos países. No hay ningún estudio presentado en toda la literatura sobre la muestra del sur de Asia, en el que todos los países realmente enfrentan el problema de la pobreza.
Keywords: Corporate governance; Financial performance; Gobierno corporativo; South Asia; Desempeño financiero; Sur de Asia; Social performance; Desempeño social; https://purl.org/pe-repo/ocde/ford#5.02.04